(untitled) (Window of Public Health Journal, 2025)
The global prevalence of malnutrition, according to the United Nations International Children’s Emergency Fund (UNICEF), affects 45.4 million children under five years old as of 2020. This study aims to explore the empowerment of Posyandu cadres in the early detection of stunting in toddlers (under two years old) in response to various stimuli. This research employs a quantitative approach, utilizing descriptive methods. The population for this study includes all 123 Posyandu cadres within the Marusu Health Center’s service area, from which a sample of 98 cadres was selected through accidental sampling. This method was implemented to ensure that the audience understands the foundational reliability of the study. The results were gathered using questionnaires and subsequently analyzed descriptively to illustrate the impact of the stimuli on the empowerment of Posyandu cadres in early stunting detection. The findings indicated that 67 respondents (68.4%) fell into the sufficient stimulus category, while 31 respondents (31.6%) were categorized as having an insufficient stimulus. Additionally, the study found that 36.7% of responses were incorrect.